2019
DOI: 10.1038/s41598-018-38405-6
|View full text |Cite
|
Sign up to set email alerts
|

Ionic current correlations are ubiquitous across phyla

Abstract: Ionic currents, whether measured as conductance amplitude or as ion channel transcript numbers, can vary many-fold within a population of identified neurons. In invertebrate neuronal types multiple currents can be seen to vary while at the same time their magnitudes are correlated. These conductance amplitude correlations are thought to reflect a tight homeostasis of cellular excitability that enhances the robustness and stability of neuronal activity over long stretches of time. Although such ionic conductanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…Temperature is not the only perturbation that crabs and lobsters experience. As with temperature, the responses of the STG to changes in pH are diverse across individuals ( Haley et al, 2018 ), again consistent with the large amount of animal-to-animal variability in the expression of ion channels ( Schulz et al, 2006 ; Temporal et al, 2014 ; Tran et al, 2019 ). It is therefore reasonable to assume that the responses to a global perturbation are diverse across individuals because different compositions of channel densities—which produce similar pyloric rhythms—are differentially resilient to any given perturbation.…”
Section: Discussionmentioning
confidence: 54%
“…Temperature is not the only perturbation that crabs and lobsters experience. As with temperature, the responses of the STG to changes in pH are diverse across individuals ( Haley et al, 2018 ), again consistent with the large amount of animal-to-animal variability in the expression of ion channels ( Schulz et al, 2006 ; Temporal et al, 2014 ; Tran et al, 2019 ). It is therefore reasonable to assume that the responses to a global perturbation are diverse across individuals because different compositions of channel densities—which produce similar pyloric rhythms—are differentially resilient to any given perturbation.…”
Section: Discussionmentioning
confidence: 54%
“…Variability in neuronal conductances underlying similar activity patterns has also been demonstrated across phyla (Swensen and Bean, 2005;Nelson and Turrigiano, 2008;Tran et al, 2019). In addition, computational modeling of the pyloric network revealed that multiple combinations of independent circuit parameters can give rise to functionally identical activity patterns (Goldman et al, 2001;.…”
Section: Variable Responses To Similar Perturbationsmentioning
confidence: 87%
“…Model half-center circuits are typically built with two identical neurons, although experimental data suggest that the conductance values and intrinsic properties of neurons even of the same type can differ significantly (Doloc-Mihu and Calabrese, 2014; Goldman et al, 2001; Marder and Goaillard, 2006; Prinz et al, 2003; Prinz et al, 2004; Roffman et al, 2012; Schulz et al, 2006; Schulz et al, 2007; Srikanth and Narayanan, 2015; Swensen and Bean, 2005; Temporal et al, 2012; Tobin et al, 2009; Tran et al, 2019). The studies in which the dynamic clamp is used to create half-center circuits from biological neurons profit from natural cell-to-cell and animal-to-animal variability to investigate circuit responses to stressors and modulators.…”
Section: Discussionmentioning
confidence: 99%